Prevalence of current chronic pain in Royal Canadian Mounted Police cadets - Robyn E. Shields; Taylor A. Teckchandani; Katie L. Andrews; Billea Ahlgrim; Danielle M. Caissie; Chet C. Hembroff; Jolan Nisbet; Gordon J. G. Asmundson; Gregory P. Krätzig; R. Nicholas Carleton (Taylor & Francis Group, 2024)
Background Nearly half of active duty Royal Canadian Mounted Police (RCMP) officers report experiencing current chronic pain (43%; i.e. pain lasting longer than 3 months). Most RCMP officers who report chronic pain indicate that the pain started after working as RCMP officers (91%). Baseline data on chronic pain prevalence among RCMP cadets has not been available.Aims The current study was designed to provide cross-sectional estimates of chronic pain prevalence among RCMP cadets starting the Cadet Training Program and to assess for sociodemographic differences among participants.Methods The RCMP Study uses a longitudinal prospective sequential experimental cohort design to create a clustered randomized trial that engages individual participants for 5.5 years. The current article provides cross-sectional associations between chronic pain prevalence and sociodemographic characteristics. Participants were RCMP cadets starting the Cadet Training Program (n = 770). Location, intensity (on a 0-10 scale and days per week experienced), and duration (number of months) of chronic pain were reported. Differences across sociodemographic characteristics were examined.Results Few RCMP cadets reported experiencing chronic pain (10%); lower back pain was rated as the most severe in terms of intensity and duration and second most frequently reported in number of days experienced per week. Prevalence of chronic pain was lower among RCMP cadets than among RCMP officers.Conclusions Chronic pain prevalence among active duty RCMP officers may result from or be moderated by operational duties, as well as routine aging. Future researchers could examine ways to mitigate chronic pain development during RCMP officer careers.